2020
DOI: 10.2176/nmc.ra.2019-0213
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Meningiomas: Review with Meta-analyses

Abstract: Observation has been a mainstay in asymptomatic meningiomas, but it may increase the risk associated with treatment due to tumor enlargement and the aging of patients. Understanding the natural course of meningiomas is important to provide appropriate treatment. The majority of previous studies investigated factors related to their growth, but failed to demonstrate their relationship with symptomatic progression (sympP) because of its rarity. We reviewed and meta-analyzed 27 studies that investigated natural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 38 publications
(180 reference statements)
2
51
1
Order By: Relevance
“…They also found initial tumor diameter of >2.5 and 3 cm went on to develop new or worsened symptoms 17% of the time. In a recent metaanalyses, Nakasu et al (12) also found large initial maximum diameter were significantly associated with symptomatic progression. As a high risk of symptom progression in large tumors, these patients may gain benefit from earlier treatment before the occurrence of symptoms.…”
Section: Natural History Of Meningiomasmentioning
confidence: 93%
See 2 more Smart Citations
“…They also found initial tumor diameter of >2.5 and 3 cm went on to develop new or worsened symptoms 17% of the time. In a recent metaanalyses, Nakasu et al (12) also found large initial maximum diameter were significantly associated with symptomatic progression. As a high risk of symptom progression in large tumors, these patients may gain benefit from earlier treatment before the occurrence of symptoms.…”
Section: Natural History Of Meningiomasmentioning
confidence: 93%
“…Recent European Association of Neuro-Oncology guidelines indicates that surgery is the first option when treatment is indicated in meningioma of any WHO grade (18). However, surgical resection is an invasive treatment, depends on tumor location and can cause significant morbidity (12). In the study of Naslund et al (19), 30-day complication rate was significantly higher among the asymptomatic cases.…”
Section: Advantage and Limitation Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Meningiomas are benign neoplasms that can exhibit a variety of growth patterns [8,9] and, eventually, 67%-75% of them enlarge [6,9,10]. In one study, tumor volume was statistically signi cantly related to the appearance of clinical symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Meningiomas are usually indolent tumors that often remain asymptomatic. 1 Even when symptomatic, approximately 80% of meningiomas are categorized as WHO grade I and slow-growing tumors that exhibit decelerated growth during enlargement. 2 However, even benign meningiomas can recur after total removal, and some of these lesions are known to behave more malignantly.…”
mentioning
confidence: 99%